2003
DOI: 10.1128/jcm.41.2.735-741.2003
|View full text |Cite
|
Sign up to set email alerts
|

Candida tropicalis in a Neonatal Intensive Care Unit: Epidemiologic and Molecular Analysis of an Outbreak of Infection with an Uncommon Neonatal Pathogen

Abstract: , two episodes of Candida tropicalis fungemia occurred in the Aristotle University neonatal intensive care unit (ICU). To investigate this uncommon event, a prospective study of fungal colonization and infection was conducted. From December 1998 to December 1999, surveillance cultures of the oral cavities and perinea of the 593 of the 781 neonates admitted to the neonatal ICU who were expected to stay for >7 days were performed. Potential environmental reservoirs and possible risk factors for acquisition of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 36 publications
(47 reference statements)
5
53
1
7
Order By: Relevance
“…Several studies have shown that positive culture of C. tropicalis to be highly predictive of subsequent systemic infection. 22 After C. tropicalis and C. albicans, C. glabrata was the third most common Candida spp. isolated (4.2%) which is similar to that of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that positive culture of C. tropicalis to be highly predictive of subsequent systemic infection. 22 After C. tropicalis and C. albicans, C. glabrata was the third most common Candida spp. isolated (4.2%) which is similar to that of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms and culture were prepared as previously described (19). C. albicans DNA was extracted as described earlier (23). Briefly, an overnight culture of C. albicans was grown on Emmons' modified Sabouraud glucose agar plate (SGA) containing chloramphenicol and gentamicin (Bioworks, Inc., Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Invasive candidiasis remains one of the leading causes of morbidity and mortality in immunocompromised and critically ill patients (1,8,9,15,18,20,23), with Candida albicans infections comprising 45% of all Candida bloodstream infections (10). Since the earliest introduction of PCR for the detection of C. albicans in blood (3,12), this technology has been increasingly refined for molecular detection of deeply invasive candidiasis.…”
mentioning
confidence: 99%
“…This was also suggested by Roilides et al 27 in a molecular epidemiologic study of an outbreak of infection caused by C. tropicalis in NICU. Mendiratta et al 5 reported no samples from NICU or hands of HCW were positive for Candida.…”
mentioning
confidence: 70%